Constraint propagation algorithms for the car sequencing problem - Lars Matthießen; Andreas Drexl; Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2000)
The car sequencing problem is to find feasible sequences of product variants requiring specific options while taking care of sequencing constraints. First, a branching scheme and constraint propagation algorithms for the computation of feasible sequences are provided. Second, an algorithm is presented which can optimize a level scheduling objective while taking care of the car sequencing constraints. Computational results are presented which show that feasible sequences can be obtained quickly for large problem instances.
Keywords: 650; Car Sequencing; Level Scheduling; Constraint Propagation Algorithms; Computational Results; Produktdifferenzierung; Scheduling-Verfahren; Just in Time; Fließfertigung; Produktionssteuerung; Theorie